2021
DOI: 10.1021/acsomega.1c00739
|View full text |Cite
|
Sign up to set email alerts
|

Alterations and Correlations of the Gut Microbiome, Performance, Egg Quality, and Serum Biochemical Indexes in Laying Hens with Low-Protein Amino Acid-Deficient Diets

Abstract: The present study was carried out to investigate the effects of methionine (Met), lysine (Lys), isoleucine (Ile), and threonine (Thr) deficiency in a low-protein diet on laying performance, egg quality, serum biochemical indices, and the gut microbiota in laying hens. A total of 300 Peking Pink laying hens, at 38 weeks of age, were randomly allocated to five dietary treatments, each of which included six replicates of ten hens. Hens were fed an amino acid-balanced diet (Met: 0.46%; Lys: 0.76%; Ile: 0.72%; Thr:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Compared with the NC group (Met 0.46%), the ADFI and ADG of Met- group (Met 0.26%) were significantly decreased during the observation period (from week seven to week 24). The result agrees with the previous studies that found that Met deficiency had significantly decreased the growth performance, such as decreased BW, FI, and increased FCR ( 26 28 ). These results showed that Met deficiency (Met 0.26%) affected the growth performance of egg-laying chicks during the rearing period and had the subsequent effect on the growth performance: BW and ADG of the Met- group were significantly decreased, but FCR was increased.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the NC group (Met 0.46%), the ADFI and ADG of Met- group (Met 0.26%) were significantly decreased during the observation period (from week seven to week 24). The result agrees with the previous studies that found that Met deficiency had significantly decreased the growth performance, such as decreased BW, FI, and increased FCR ( 26 28 ). These results showed that Met deficiency (Met 0.26%) affected the growth performance of egg-laying chicks during the rearing period and had the subsequent effect on the growth performance: BW and ADG of the Met- group were significantly decreased, but FCR was increased.…”
Section: Discussionsupporting
confidence: 93%
“…For a long time, Met has been used as a feed additive in livestock and poultry diets to maintain animal health and growth performance. According to previous studies, because of the lack of essential amino acids in low protein diets, production performance and egg quality are negatively affected, the intestinal morphology is damaged, and the immune response level is reduced (41)(42)(43). In this study, Peking Pink laying hens were selected as the experimental model to explore the effects of different levels of Met in the low protein diet on the performance, egg quality, serum biochemical indexes, and gut microbial composition of the laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…The Haugh unit, yolk color, and egg weight were measured by a multifunctional egg quality tester (EA-01; Orka Food Technology Ltd., Ramat Hasharon, Israel). The eggshell was weighed, and yolks were separated using a separator and were then weighed to determine the relative yolk and albumen proportion as previously described ( 34 ).…”
Section: Methodsmentioning
confidence: 99%